Barack Obama : an American story - Edwards, Roberta; Call, Ken (New York Scholastic, 2008)
A brief biography of Senator Barack Obama who was running as a presidential candidate for the Democratic Party.
M
680
M
Keywords: Obama, Barack -- Juvenile literature; Obama, Barack; United States. -- Congress. -- Senate -- Biography -- Juvenile literature; United States. -- Congress. -- Senate. -- Biography; African American legislators -- Biography -- Juvenile literature; Legislators -- United States -- Biography -- Juvenile literature; Presidential candidates -- United States -- Biography -- Juvenile literature; Racially mixed people -- United States -- Biography -- Juvenile literature; Legislators; African Americans -- Biography; Presidential candidates; Racially mixed people -- Biography